The Relationship Of Allowance, Knowledge, And Attitude In Choosing Snack With Snack Consum+ption For Students In Grade 4-6 At UPT SDN 154 Gresik - Emalia Lestari; Choirul Anna Nur Afifah (Jurnal Gizi dan Kesehatan Nusantara, 2024)
Snacks are a familiar food among school-age children. In a day, children spend about a quarter of their time at school, so parents give them pocket money every day. The size of the pocket money that children have at school determines their purchasing power for food. Currently, snacks are so diverse that even school-aged children are interested in consuming them. Often they are negatively impacted by snacks that do not meet the requirements while at school because they do not have enough knowledge to recognize safe snacks. Thewaim of this research is to determine the relationship between the amount of pocket money, knowledge and attitudes in choosing food with food consumption among students in grades 4-6 at UPT SDN 154 Gresik. This research uses quantitative methods with a cross sectional plan. A sample of 64 students was takenwusing saturated sampling techniques. Datawanalysis using the Spearman Rank correlation test revealed that there was no relationship between the amount of pocketwmoney and the consumption of snacks among students in grades 4-6 at UPT SDN 154 Gresik (p=0.054). There is a relationship between attitudes regarding the choice of snack foods and consumption of snack foods among students in grades 4-6 at UPT SDN 154 Gresik (p=0.023). Meanwhile, it is known that data analysis using the Chi Square correlationwtest shows that there is a relationship between knowledge regarding the choice of snack foods and consumption of snack foods among students in grades 4-6 at UPT SDN 154 Gresik (p=0.017).